18F-fluorodeoxyglucose positron emission tomography/computed tomography in predicting overall survival of oral cavity squamous cell carcinoma: Ongoing controversy - Stephen Scott; J Byrd; Ramon Figueroa; Hadyn Williams; Jie Chen; Jaeeun Lee; Darko Pucar (World Journal of Nuclear Medicine)
We aimed to retrospectively determine if initial staging 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) can predict overall survival (OS) in oral cavity squamous cell carcinoma (OCSCC), which is currently a source of ongoing controversy in the literature. Forty-six consecutive patients with nonmetastatic (Stage M0) OCSCC had 18F-FDG PET/CT prior to definitive surgical treatment followed by observation or adjuvant treatment at our institution between 2006 and 2012. The median follow-up time was 18 months (range 0.1–76 months). Univariate and multivariate analysis were used to determine the ability of imaging, pathologic, and demographic factors to predict OS. 18F-FDG PET/CT parameters were standardized uptake value (SUV) maximum and mean, metabolic tumor volume, and total lesional glycolysis (TLG) of primary tumor and regional nodes. Significant predictors of OS in the multivariate analysis were primary tumor SUV mean, nodal TLG, and age. Two-year OS of patients with primary tumor SUV mean below and above the median of 6.26 was 68% and estimated 28%, respectively. Two-year OS of patients with nodal TLG below and above median of 7.9 was 69% and 34%, respectively. Two-year OS of patients younger and older than median age of 57 was 60% and 43%, respectively. Our results suggest that 18F-FDG PET/CT may be a valuable addition to multifactorial models predicting outcome for OCSCC. Thus, continued research aiming to incorporate 18F-FDG PET/CT parameters in risk-stratification algorithms for OCSCC is warranted and should be conducted using more standardized prognostic models driven by a specific clinical question.